Persepsi Siswa terhadap Pengembangan Budaya Organisasi di SMAN 13 Surabaya - Rahhmawati, Rofiqotur Rista; Sabirin, Reina; Pratama, Rodeo Novandi; Trihantoyo, Syunu; Nuphanuddin, Nuphanuddin (Lembaga Yasin AlSys, 2024)
Organizational culture is a unified system of values that is adhered to and used as guidelines by an organization. Very organizational culture important for achieving organizational effectiveness. Cultural implementation School organization is not much different from the implementation of culture organization in general. Apart from functioning as a school identity what differentiates one school from another, Organizational culture can become a standard of behavior for school citizens influencing the school community to take action experienced. Development of a strong, intimate, conducive organizational culture, and being responsible will provide various benefits for all school residents. This article aims to analyze how students are towards the development of organizational culture in the SMAN environment 13 Surabaya. The method used in this research is qualitative descriptive. The data collection technique used is interviews and questionnaires. The research results show that the development of organizational culture is very influential and important towards SMAN 13 Surabaya, this is proven by culture The organization influences the final results expected by the parties' school as well as being the foundation for implementing internal activities school organization.